Profitability or Value? Rethinking the Link in Public Companies (Literature Review) - Nugroho, Yohanes Vianney Ario; Clarinta, Avika Anno; Putra, Febrianur Ibnu Fitroh Sukono; Gunawan, Yosaf Andrew; Yulianto, Ahmad Rudi (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2024)
This study explores the relationship between profitability and firm value in public companies in Indonesia, with capital structure examined as a mediating factor. A literature-based approach was employed by synthesizing findings from national and international research, emphasizing indicators such as Return on Assets (ROA), Return on Equity (ROE), Price to Book Value (PBV), and Tobin’s Q. The results reveal that profitability generally has a positive impact on firm value, yet this effect is not always consistent due to the role of capital structure. High leverage can weaken or even offset the benefits of profitability, while optimal capital structure enhances market valuation. The study provides theoretical contributions to corporate finance and practical implications for managers, investors, and policymakers.